2003
DOI: 10.1073/pnas.2131556100
|View full text |Cite
|
Sign up to set email alerts
|

Human uptake and incorporation of an immunogenic nonhuman dietary sialic acid

Abstract: Humans are genetically unable to produce the sialic acid N-glycolylneuraminic acid (Neu5Gc), because of a mutation that occurred after our last common ancestor with great apes. Although Neu5Gc is presumed absent from normal humans, small amounts have been claimed to exist in human tumors and fetal meconium. We have generated an antibody with high specificity and avidity for Neu5Gc. Fetal tissues, normal adult tissues, and breast carcinomas from humans showed reactivity to this antibody, primarily within secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
586
3
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 543 publications
(612 citation statements)
references
References 48 publications
18
586
3
1
Order By: Relevance
“…To determine the relative importance of Sia-specificity, we experimentally changed the Sia profile while keeping the glycophorin protein backbone constant. Human cells growing in human serum express only Neu5Ac but can metabolically incorporate free Neu5Gc from the medium and eventually express it on their membrane glycoconjugates (41,46,47). The human erythroleukemia cell line K562 is known to express GYPA (48), and we found that it also expresses glycophorin C [both were detected by specific antibody staining and flow cytometry (data not shown)].…”
Section: Recombinant Pfeba-175 and Preba-175 Riis Show Sia-dependentmentioning
confidence: 79%
“…To determine the relative importance of Sia-specificity, we experimentally changed the Sia profile while keeping the glycophorin protein backbone constant. Human cells growing in human serum express only Neu5Ac but can metabolically incorporate free Neu5Gc from the medium and eventually express it on their membrane glycoconjugates (41,46,47). The human erythroleukemia cell line K562 is known to express GYPA (48), and we found that it also expresses glycophorin C [both were detected by specific antibody staining and flow cytometry (data not shown)].…”
Section: Recombinant Pfeba-175 and Preba-175 Riis Show Sia-dependentmentioning
confidence: 79%
“…Glycan 20, which is an ␣2-6 monosialylated derivative of NA2, bound RCA-I before and after neuraminidase, although binding was not enhanced after neuraminidase treatment. RCA-I bound weakly to ␣2-6-sialylated lactose and LNnT (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), unlike the corresponding ␣2-3-sialylated lactose and LNnT (41-57), which were not bound. Although most sialic acid derivatives moderately decreased RCA-I binding to NA2, ␣2-6-sialylation with Neu5Ac8Me (19) and Neu5Gc9Ac (25) greatly inhibit RCA-I binding.…”
Section: Resultsmentioning
confidence: 99%
“…8,10,44,53,60 Even though Neu5Gc is a common sialic acid in most mammals, it has been demonstrated to be absent in healthy humans and only small amounts have been found in some tumors and meconium. 61 The CE-MS method succeeded in detecting this heterogeneity of acidic monosaccharides without removing the sialic acid from the glycan chain by acid hydrolysis as it has been commonly reported. 8,53,62 As reviewed lately, the LC-MS detection of sialic acids and its heterogeneous subtypes is challenging.…”
Section: Detection Of Glycan Modifications In Rhuepomentioning
confidence: 96%